Metabolic Alterations in Experimental Autoimmune Encephalomyelitis in Mice: Effects of Prior Physical Exercise - Bernardes, D.; Oliveira-Lima, O.C.; Da Silva T. Vitarelli; Juliano, M.A.; Dos Santos D. Moreira; Carvalho-Tavares, J. (Нейрофизиология, 2016)
Experimental autoimmune encephalomyelitis (EAE) induces significant reduction of the body mass concomitant to sickness behavior and anorexia. We investigated whether regular physical exercise prevents metabolic alterations associated with loss of the body mass occurring during an EAE inflammatory peak. Female C57BL/6 mice were assigned to the unexercised and exercise-trained groups. In four weeks, EAE was induced in half of the animals in each group, and the exercise protocol was maintained onto 10 days post-induction (10 dpi) completing 6 weeks of regular exercise (forced swimming). At 14 dpi, the relative mass of metabolic tissues, serum levels of triglycerides, cholesterol, and glucose, glycogen contents in the muscle and liver, and muscle levels of cytokines were measured. A significantly decreased clinical score associated with attenuation of the body mass loss in exercised EAE animals, as compared to the non-exercised ones, were observed. The associated metabolic parameters were not modified by this approach, although negative correlations between some parameters and clinical score at 14 dpi were observed. Although the prior program of aerobic exercise is capable of decreasing clinical score and body mass loss, it is not sufficient to crucially modify metabolic outcomes associated with inflammation at the EAE peak.